OPERATIONAL STANDARD PROCEDURE, FOR MANAGERIAL ASPECTS AND OPERATIONAL STANDARD PROCEDURES ABOUT THE WORK PROCESS - Muliati (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal